1977
DOI: 10.1073/pnas.74.1.360
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of blood pressure and vascular collagen in hypertensive rats by beta-aminopropionitrile.

Abstract: #-Aminopropionitrile, a specific inhibitor of lysyl oxidase preventedthe rise in blood pressure induced by deoxycorticosterone-salt in rats. In addition, after the onset of hypertension, administration of P-aminopropionitrile lowered the blood pressure. Concomitant with the lowering of blood pressure, there was a reduction in the more highly crosslinked form of vascular collagen. These findings would indicate that increases in vascular connective tissue are not only sequelae of hyprtension, but may also contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
2

Year Published

1978
1978
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 16 publications
(10 reference statements)
4
23
2
Order By: Relevance
“…In addition, the lower expression of elastase and cathespin L observed in SHR suggests a difference in the regulation of the vascular extracellular matrix system (20,42). The reduction in expression of elastase in the current study is consistent with a reported reduction in blood pressure observed in SHR after injection of elastase (18). The altered expression of matrix genes appears to begin early in the SHR animals, since the differences between strains were apparent at 3 wk of age.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In addition, the lower expression of elastase and cathespin L observed in SHR suggests a difference in the regulation of the vascular extracellular matrix system (20,42). The reduction in expression of elastase in the current study is consistent with a reported reduction in blood pressure observed in SHR after injection of elastase (18). The altered expression of matrix genes appears to begin early in the SHR animals, since the differences between strains were apparent at 3 wk of age.…”
Section: Discussionsupporting
confidence: 80%
“…Aging is associated with many vascular changes, such as a rise in arterial stiffness, smooth muscle cell hypertrophy, and fibrosis (22). The regulation of expression of extracellular matrix proteins is important in the elastic properties of the vascular system, and an age-related increase in aortic stiffness has been observed in SHR (2,14,18,26,47,49). Interestingly, we observed significant changes in the expression of several connective tissue genes from 3 to 9 wk of age in both WKY and SHR; however, the levels of procollagen (type I and II) and collagen (type I) were higher in SHR at both 3 and 9 wk of age.…”
Section: Discussionmentioning
confidence: 99%
“…27 /3-Aminopropionitrile, an inhibitor of lysyl oxidase, an enzyme necessary for crossUnking in collagen and elastin, also reduced aortic collagen biosynthesis in hypertensive rats and lowered the blood pressure as well. 7 Our studies on the SHR with well-established hypertension indicated that changes in the vascular connective tissue composition did not occur following antihypertensive drug therapy.…”
Section: Discussionmentioning
confidence: 99%
“…5 The spontaneously hypertensive rat (SHR) appears to be a useful animal model to study human essential hypertension as judged by several physiological and pathological criteria. 6 Comparative studies on aortic tissue between the SHR and normotensive control rats have shown differences in several biochemical processes including connective tissue metabolism, 7 cyclic nucleotide metabolism, 8 ' 9 glycolytic and lysosomal enzyme activity, 10 ' n norepinephrine metabolism, 12 and calcium uptake. 13 ' 14 The present study was conducted to determine whether biochemical differences in aortic tissue between the SHR and the normotensive WistarKyoto (WKY) rats were affected by the reversal of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…To inhibit collagen deposition in the vascular and extravascular myocardial tissue, we superimposed /3-aminopropionitrile (/3-APN) treatment on ascending aortic banding for 10 weeks in rats. In experimental models of systemic 13 and pulmonary 14 " 16 hypertension, inhibition of collagen deposition by /3-APN lowered the blood pressure. Collagen deposition in the vascular wall plays a key role in sustaining the high blood pressure of the systemic or pulmonary circulation.…”
Section: Collagen Deposition and The Reversal Of Coronary Reserve In mentioning
confidence: 99%